MODEL PEMBERDAYAAN MASYARAKAT MELALUI BUDIDAYA SAWI PAGODA BERBASIS PEKARANGAN RUMAH DI DESA PASIGARAN, SUMEDANG - Murgayanti Murgayanti; Intan Ratna Dewi Anjarsari; Uum Umiyati; Alifiyan Anur (Jurnal Abdi Insani, 2025)
The utilization of home-yard space holds substantial potential to enhance household food security and economic resilience in rural areas. However, limited community knowledge of cultivation techniques often results in suboptimal use of available land. This community service program aims to improve the knowledge and skills of residents in Pasigaran Village through training on the cultivation of pagoda mustard (Brassica narinosa L.). The program was implemented through counseling sessions, technical demonstrations, and hands-on field practice involving 14 members of the Women Farmers Group (KWT). Evaluation was carried out using pre-test and post-test assessments to measure improvements in participants’ knowledge and interest. The results indicate significant increases across all measured variables. Knowledge of pest and disease control improved from 18.8% to 93.8%, understanding of cultivation prospects increased from 0% to 100%, and prior planting experience rose from 7.1% to 85.7%. Interest in pagoda mustard cultivation also increased from 71.4% to 100%. Participants were able to apply the cultivation techniques independently through the establishment of home-yard demonstration plots. This program is concluded to be effective in enhancing community capacity and promoting the utilization of home-yard space as a source of food and potential household income.